Asthenospheric flow through the Izanagi-Pacific slab window and its influence on dynamic topography and intraplate volcanism in East Asia - Brown, Hamish; Colli, Lorenzo; Bunge, Hans-Peter (Frontiers in Earth Science, 2022)
The tectonics of East Asia are notoriously complex. Consisting of an intricate patchwork of microplates and accreted terranes, even the Cenozoic tectonic history of the region remains controversial, and many differing reconstructions have been proposed. While the exact kinematics remain poorly constrained, it is generally accepted that East Asia has been characterised by a long history of subduction and downwelling. However, numerous geological observations, at a first glance, appear to lie in stark contrast to this history. For example, seismically slow anomalies in the uppermost mantle are extensive in this region and correlate spatially with widespread intraplate volcanism since the latest Paleogene, which is seemingly at odds with the cold upper mantle and downwelling flow expected from a history of subduction. Here, we propose a solution to this paradox, in which hot asthenospheric material flows through the slab window opened by the subduction of the Izanagi-Pacific ridge during the early Cenozoic, passing from the Pacific domain into East Asia. To investigate this hypothesis, we compare several independent geological observations to the asthenospheric flow predicted by a suite of recently published global mantle circulation models. The timing and location of intraplate volcanism is compared with the predicted distribution of this hot material through time, while observations linked to uplift and erosion are compared to the changes in dynamic topography that it induces. These include the widespread late Eocene–Oligocene sedimentary hiatus in far eastern China and the regional erosion of the South China Block since the Miocene inferred from Apatite Fission Track Thermochronology studies. The westward influx of hot asthenospheric material is a robust feature in the models, being predicted regardless of the implemented Cenozoic tectonic reconstruction. However, we find that a small Philippine Sea Plate (PSP) that overrides a marginal 'vanished ocean' during the late Cenozoic provides an optimal fit to the geological observations considered. Flow of hot asthenospheric material through gaps in subduction has the potential to significantly affect the geodynamic and geologic history of backarc and hinterland regions, and might have been a recurring phenomenon throughout Earth's history. However, further research will be required in order to establish this.